Double trapper technique: A novel technique to facilitate retrograde wire externalization in aorto‐ostial chronic total occlusion intervention without using snare. Issue 1 (25th March 2019) - Chan, Chi Yuen; Chan, Yu Ho
Abstract: Chronic total occlusion (CTO) remains a technical challenge for the interventional cardiologists. The application of the retrograde approach has dramatically improved success rates of CTO PCI. However, retrograde wire externalization could be very difficult especially when the antegrade guiding catheter cannot sit into the coronary ostium stably. We report a novel technique to facilitate retrograde wire externalization in aorto‐ostial chronic total occlusion intervention without using snare.